Synthesis of zeolite from coal fly ash by hydrothermal method without adding alumina and silica sources: effect of aging temperature and time - W. Chansiriwat; D. Tanangteerapong; K. Wantala (Penerbit Universiti Kebangsaan Malaysia, 2016)
The aim of this research was to synthesize zeolite from coal fly ash by hydrothermal method. The effect of aging temperature and time on zeolite P1 synthesis (Na-P1) from Mae Moh coal fly ash (MFA) without adding any alumina and silica sources were examined during the synthesized process. The central composite design (CCD) was used for experimental design to obtain the optimal process parameters of the aging temperature (105-195ºC) and time (12-84 h) where the specific surface area was used as a response. The chemical and physical properties of Na-P1 such as specific surface area, crystalline phase, compositions and morphology were examined. The response results showed that the specific surface area of Na-P1 decreased with an increase of both aging temperature and time, whereas the XRD intensity of Na-P1 increased with an increase of both aging temperature and time. The composition of SiO2/Al2O3 in mass ratio of coal fly ash was observed, which was suitable to Na-P1 synthesis. The maximum specific surface area of zeolite products was found at the designed condition of aging temperature of 105ºC and time of 12 h. Thus, zeolite P1 can be prepared by hydrothermal method without adding any alumina and silica sources.